Vertical Nitrate Flux Induced by Kelvin–Helmholtz Billows Over a Seamount in the Kuroshio - Acabado, Cristy S.; Cheng, Yu-Hsin; Chang, Ming-Huei; Chen, Chung-Chi (Frontiers in Marine Science, 2021)
Kelvin–Helmholtz (KH) billows can facilitate microscale turbulent mixing around seamounts in the Kuroshio. This study sought to describe the influence of billow intensity (i.e., “intermittent and small” and “steady and large” billows) on vertical nitrate fluxes. KH billows led to turbulent kinetic energy dissipation rates [ε = O (10–7 to 10–6) W kg–1] and eddy diffusivities [Kρ = O (10–4 to 10–3) m2 s–1] that were significantly stronger than those outside the billow depths. The mean nitrate flux estimated using Kρ in the billow depths had a maximal value of 10.0 mmol m–2 day–1, which was much higher than estimates for the open ocean. The nitrate flux associated with the shallow KH billows at two vertical levels contributed to enrich the subsurface phytoplankton maximum, while the deeper billows closer to the summit were found to induce a large amount of nitrate flux from the deeper to the subsurface water. This study showed that KH billows make important contributions to seamount ecosystems, particularly in the cycling and vertical mixing of nutrients to make them available for potential downstream transport.